Venice in Polish Literature of the Latter Half of the 16th Century and in the 17th Century as a Model Political System, a Leading Centre in the Fight Against the Ottoman Empire, and the Centre of the Pilgrimage Culture - Kuran , Michał (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The aim of the study is to present at least three reasons why Old Polish writers of the latter half of the 16th century and 17th century wrote about Venice. The first one was the admiration in the nobility-ruled republican political system which emerged in the Republic of Venice, and which was considered as an attractive model by Old Polish thinkers and writers. They, e.g. Palczowski, Górnicki, and Wolan, expressed their convictions in their treatises. The second reason was that of the struggles of Christian states with the Ottoman Empire. Venice constituted the first potential ally and often a leader of European armies intended to participate in the often-planned anti-Muslim crusades. The study references the accounts of the visions of Venice as a leader of crusades as inscribed in the exhortation-related literature. The third reason was the perception of Venice as a safe port for pilgrims travelling to the Holy Land and, more broadly, to the territory of the Ottoman state via the sea. Its image emerged from the accounts of Old Polish pilgrims, travellers, and escaped slaves.